O Controle da Deriva Litorânea no Desenvolvimento do Campo de Dunas e da Antepraia no Litoral Médio do Rio Grande do Sul - TOLDO JR, ELÍRIO; ALMEIDA, LUIZ; NICOLODI, JOÃO L; ABSALONSEN, LUCIANO; GRUBER, NELSON (Pesquisas em Geociências, 2006)
<!-- .p { text-align: justify; } --> Zones of erosion and accretion were delimited by comparing a DGPS shoreline mapping in 1997 and the beach line reproduced from the army chart collection of 1975. The results show extensive shore retreat along of Rio Grande do Sul central coast, while accretion was observed in Mostardas and Dunas Altas beach. Mathematical estimative of the regional longshore transport potential along the Rio Grande do Sul coast, a 630-km long holocenic fine sand barrier, resulted in a large net northward annual sand volume. Additionally, the estimated potential of sediment transport based on the CERC formula predicts a substantial variation of the energy flux into the surf zone, due to little changes in shoreline alignments and in the potential alongshore sediment transport. The reduction in the sediment flux due to changes in the shoreline alignment produce a jam in the longshore transport, meaning that part of the sediment arriving from the upstream stretch may be deposited or diverted offshore by coastal jet. Based on that, it is possible that changes in the net longshore sand transport are responsible for the increase in the shoreface width from less than 1 km to more than 3 km in Mostardas beach and Dunas Altas beach. Interesting to note that wider dune fields are associated to those beaches where shoreface is also wider. In this way, the volume of longshore sand transport and the sediment jam provide by changes on shoreline alignment in Mostardas and Dunas Altas beaches are important for both coastal dune fields and shoreface width.